PENGEMBANGAN MEDIA PEMBELAJARAN ANDROID BERBANTUAN MIT APP INVENTOR UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Andreas Jones r sitompul; Roza Thohiri; Andri Zainal; Haryadi; Ali Fikri Hasibuan (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research was motivated by the low learning motivation of students in accounting subjects. The study aims to develop Android-based learning media using MIT App Inventor that is feasible, practical, effective, and can improve learning motivation of grade XI AKL students at SMK Negeri 1 Medan. This development research used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and involved 32 students of class XI AKL 1 in the 2025/2026 academic year. Data were collected through interviews, observations, questionnaires, and documentation. The media was validated by material experts (98%), media experts (90%), and practitioner experts (95%). Student responses showed the media was effective (82%). Motivation improvement was proven through a t-test, with t-count = 29.149 > t-table = 2.0395 and Sig. = 0.000 < 0.05. The developed media includes interactive content accessible via Android, facilitating independent and engaging learning. The results confirm that the Android-based learning media assisted by MIT App Inventor is feasible, effective, and significantly increases students' motivation in learning financial accounting, particularly on fixed asset material